2017
DOI: 10.1186/s13075-017-1372-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the response to tumor necrosis factor inhibitors in axial spondyloarthritis

Abstract: BackgroundFew studies have investigated the impact of obesity on the response to tumor necrosis factor inhibitors (TNFi) in patients with axial spondyloarthritis (axSpA). The aim of our study was to investigate the impact of different body mass index (BMI) categories on TNFi response in a large cohort of patients with axSpA.MethodsPatients with axSpA within the Swiss Clinical Quality Management (SCQM) program were included in the current study if they fulfilled the Assessment in Spondyloarthritis International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 22 publications
1
54
0
4
Order By: Relevance
“…A similar tendency toward higher efficacy was observed in Asian patients who participated in the global secukinumab AS studies [29]. It has been reported that obesity negatively affects the outcome of axial SpA patients treated with anti-TNF agents [30] and secukinumab clearance and volume of distribution vary with body weight [31]; therefore, in addition to the design of open-label study, the overall lighter patient weights in MEASURE 2-J could have contributed to the positive treatment outcome. In this study, ASAS responses were higher in the subgroup of patients with body weight less than 70kg than in the 70-90 kg subgroup.…”
Section: Discussionmentioning
confidence: 52%
“…A similar tendency toward higher efficacy was observed in Asian patients who participated in the global secukinumab AS studies [29]. It has been reported that obesity negatively affects the outcome of axial SpA patients treated with anti-TNF agents [30] and secukinumab clearance and volume of distribution vary with body weight [31]; therefore, in addition to the design of open-label study, the overall lighter patient weights in MEASURE 2-J could have contributed to the positive treatment outcome. In this study, ASAS responses were higher in the subgroup of patients with body weight less than 70kg than in the 70-90 kg subgroup.…”
Section: Discussionmentioning
confidence: 52%
“…Published literature has demonstrated that high BMI/obesity may negatively impact the response to TNF inhibitors [23][24][25] and that the presence of baseline autoantibodies and autoantibody levels have been correlated with clinical responses. In the AMPLE trial, baseline ACPA positivity (versus ACPA negativity) as measured by an anti-CCP2 ELISA was associated with better responses to abatacept or adalimumab; patients with the highest baseline ACPA antibody concentrations had better clinical response to abatacept than patients with AE adverse event, N population size, n number in group, QD daily, ROW rest of the world, SAE serious adverse event, US United States including Puerto Rico a Includes data up to rescue.…”
Section: Discussionmentioning
confidence: 99%
“…Micheroli et al concluded that BMI affects response to TNFis in axSpA patients, in that study, results demonstrated that obesity was associated with signi cantly lower response to the aforementioned class of therapeutic agents [24]. Moreover, a French study conducted by Malochet-Guinamand et al found that axSpA patients with lower BMI had lower BMD [25].…”
Section: Discussionmentioning
confidence: 84%